Improved Solar Cell Energy Backup Supply Protection System in Households - Firza Ardana; Arya Pratama; Supri Ananda; Barus, Yovie Ade Alvian; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
Utilization of solar energy through Solar Power Plants (SPP) is an alternative technology that is usually used at home. In this context, the journal "Security System with Solar Panel Energy Backup for Households". In this study, it discusses the increase in protection that is implemented as a household security system that uses solar panel energy backup. The research methods used include literature study, system design, system implementation, system testing, and result analysis. It is hoped that this journal can contribute to the development of household security technology that is environmentally friendly and energy efficient.